The Influence of Tourist and Recreation Activities on State of Greenzones of the Lviv Urban Ecosystem - Гілета, Лобов Андріївна (Київський національний університет імені Тараса Шевченка, 2019)
The aim of the study. Research the tourism and recreational activities of residents and visitors of the city of Lviv regarding the ecological state of green zones which perform a number of important functions, including social and environmental, which is to ensure that the residents of the city have the most favorable environmental conditions. Method. It is analized that within the Lviv urban ecosystem a green zone is allocated, that is, a system of territories with green plantations in unoccupied open spaces within a city or suburban area which have ecological, economic, recreational and aesthetic importance. The tourist and recreational use of the green zone has a significant negative impact on its condition. Results. The tourist and recreational activity of the residents of the Lviv urban ecosystem within the green zones is shown in walks, with pets included, mostly on unauthorized trampled trails, in organizing picnics, usually with the burning of fires, sports games and sunbathing and other, however, it is somewhat different depending on the type of green area and its affiliation with the nature reserve. Accordingly, the green areas of the Lviv urban ecosystem are exposed to such environmental effects as trampling of grass, which in turn leads to compaction of soil, compaction of the layer beneath, death of descending plants; collection of individual plants (usually flowers), which reduces the possibility of their self-renewal; mechanical damage to the green planting - a broken branch, kerf or notch on the trunk which cause infection of the trees with diseases and pests; contamination of the territory; burning of the upper layers of soil through unauthorized arrangement of fires, etc. Scientific novelty. Here is described the ecological consequences of the impact of tourist and recreational activities, which are quite large in local terms. Practical importance. It is stated that within the limits of the greenzones of the Lviv urban ecosystem, it is forbidden to damage and destroy trees, grass cover and equipment, consider a camp fire, arrange unauthorized rest places, passage and parking of transport, walk animals. But in order to reduce the negative impact of tourism and recreational activity on the state of the green zones of the urban ecosystem of Lviv, it is also necessary to introduce a system of management of the green zones of the city, which is, to create an interested administration.The wellestablished actions of the administration contribute primarily to the demarcation of the territory of the green areas, as well as to reduce the negative demonstration of recreational use of green areas.

Мета. Описати дослідження впливу туристично-рекреаційної діяльності жителів та гостей міста Львова (чисельність яких постійно зростає) на екологічний стан зелених зон, які виконують ряд важливих функцій, зокрема соціально-екологічну, що полягає в забезпеченні мешканців міста максимально сприятливими умовами навколишнього середовища. Методика. Проаналізовано зелену зону, що виділяється в межах Львівської урбоекосистеми. Це система територій із зеленими насадженнями на незабудованих відкритих просторах в межах міста або приміської зони, що мають екологічне, економіко-господарське, рекреаційне та естетичне значення, туристично-рекреаційне використання якої має значний негативний вплив. Результати. Туристично-рекреаційна діяльність мешканців Львівської урбоекосистеми в межах зелених зон проявляється у прогулянках, в тому числі і з домашніми улюбленцями, переважно самовільно протоптаними стежками, у організації пікніків, зазвичай із розпалюванням вогнищ, спортивних ігор та місць для приймання сонячних ванн та ін., однак дещо відрізняється залежно від типу зеленої зони та її приналежності до об’єктів природно-заповідного фонду. Відповідно зелені зони Львівської урбоекосистеми зазнають таких видів екологічного впливу як витоптування трав’яного покриву, що надалі призводить до ущільнення ґрунту, спресовування підстилки, загибелі рослин, що зійшли; збір окремих рослин (зазвичай квітів), що зменшує можливість самовідновлення рослин; механічне пошкодження зелених насаджень – зламана гілка, зарубка чи насічка на стовбурі спричинюють зараження дерев хворобами та шкідниками; засмічення території; вигорання верхніх шарів ґрунту через самовільне облаштування вогнищ та ін. Наукова новизна. Описано екологічні наслідки впливу туристично-рекреаційної діяльності, які досить масштабні в локальному відношенні. Практична значимість. Зазначено, що в межах зелених зон Львівської урбоекосистеми на законодавчому рівні забороняється пошкодження і знищення дерев, трав’яного покриву і обладнання, розглядання багаття, організація стихійних місць відпочинку, проїзд і стоянку автомобільного транспорту, вигул тварин. Але для зменшення негативного впливу туристично-рекреаційної діяльності на стан зелених зон урбоекосистеми Львова необхідно також запровадити функціонування системи управління зеленими зонами міста, тобто створити зацікавлену адміністрацію. Налагоджені дії останньої сприяють перш за все проведенню демаркації території зелених зон, а також зменшенню негативних проявів рекреаційного використання зелених зон.
Вплив туристично-рекреаційної діяльності на стан зелених зон львівської урбоекосистеми
Keywords: зелена зона; туристично-рекреаційна діяльність; екологічний вплив; green zone; tourist and recreational activity; ecological development